2007
DOI: 10.1002/adma.200600961
|View full text |Cite
|
Sign up to set email alerts
|

A General Route to Printable High‐Mobility Transparent Amorphous Oxide Semiconductors

Abstract: Inkjet printing of inorganic materials for the formation of active devices is relatively rare compared to the research done with respect to organic materials. To date, only a handful of inorganic materials have been ink-jet printed, primarily because of the difficulty in preparing ink-jet-printable precursors. We have developed a general and low-cost route to the ink-jet printing of transparent amorphous oxide semiconductors. Our process uses metal halide precursors dissolved in acetonitrile, an organic solven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
318
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 404 publications
(323 citation statements)
references
References 13 publications
4
318
0
1
Order By: Relevance
“…An aqueous route allows for the preparation of IZO TFTs at a lower temperature compared with that used in the previously reported 2-methoxyethanol-based approach. [10][11][12] To investigate the uniformity of the devices, 36 TFTs with an IO active layer prepared via the aqueous route were fabricated at an The storage stability of a precursor solution is an important issue in sol-gel chemistry. The TFTs fabricated from pristine and 100-day-old aqueous solutions were compared with investigate the storage stability of the aqueous solution.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An aqueous route allows for the preparation of IZO TFTs at a lower temperature compared with that used in the previously reported 2-methoxyethanol-based approach. [10][11][12] To investigate the uniformity of the devices, 36 TFTs with an IO active layer prepared via the aqueous route were fabricated at an The storage stability of a precursor solution is an important issue in sol-gel chemistry. The TFTs fabricated from pristine and 100-day-old aqueous solutions were compared with investigate the storage stability of the aqueous solution.…”
Section: Resultsmentioning
confidence: 99%
“…The high annealing temperature, which is usually 4400 1C, is not compatible with flexible plastic substrates, with conventional glass or with the stacked multi-layer structures because of the mismatch in the coefficient of thermal expansion between the layers during deposition. [10][11][12] A few studies on low-temperatureprocessable MOSs have been reported. [13][14][15][16] However, the authors of these studies used either complex and unstable precursors that required significant effort and multiple steps for synthesis or complicated chemical reactions that are not appropriate for the general fabrication technique.…”
Section: Introductionmentioning
confidence: 99%
“…Oregon State University and Hewlett-Packard reported the fabrication of a-ZIO TFT from a metal halide source with post-thermal annealing at 400 °C [56], and the preparation of a-ZTO and a-ZIO with thermal annealing at 500 °C [57] and a-IGZO with thermal annealing at 450 °C [58]. Recently, wet process technology has been improved signifi cantly, and the lowest annealing temperature of 280 °C and the highest mobility of 28 cm 2 /V s for 600 °C-annealed a-IGZO TFT were recently reported [59].…”
Section: Materials and Processesmentioning
confidence: 99%
“…For example, metal oxides such as zinc oxide (ZnO) [17][18][19][20][21][22] , indium oxide (In 2 O 3 ) [23][24] , indium gallium oxide (InGaO) [25] , indium zinc oxide (InZnO) [18][19][20][21][22][23][24][25][26] and zinc tin oxide (ZnSnO) [27] have been synthesised using soluble precursors and implemented into TFT structures. Despite the process simplicity, excellent charge carrier mobilities have been achieved, clearly demonstrating the significant potential of this alternative processing methodology.…”
mentioning
confidence: 99%